Editorial - Khan, Israr Ahmad (International Islamic University Malaysia, 2015)
Journal of Islam in Asia (JIA) is devoted right from its first issue in 2004 to publication of quality research papers in both Arabic and English. Research denotes thorough investigation into and deliberation over an issue with a view to developing a totally novel idea or suggesting new interpretation of the currently existing idea. Mere compilation of various views from different quarters, or collection of materials on the issue concerned, or translation of a known or unknown work into another language may not be considered by the academia research.